PENGGUNAAN TEKNIK APROKSIMASI (METAMODELING) UNTUK MENYEDERHANAKAN MODEL ELEMEN HINGGA DALAM PROSES OPTIMASI - Rachman Setiawan (Mesin, 2005)
Complex modelling using Finite element method in iterative optimisation process often yield expensive computation. One of the solution is to replace the expensive finite element analysis with a mathematically simpler model, that is using an approximate relations (Metamodel). Here, the approach is used to characterise the mechanical properties of an anisotropic plate from their corresponding natural frequencies. Radial basis functions model has been chosen for the Metamodel to approximate the finite element model generated in ANSYS 6.1 software. Characterisation process is regarded as an optimisation problem with the objective is to minimise the accumulation of differences between the target frequencies and the updated ones. The use of Metamodel shorten the computation time as well as increase the likelihood of reaching the global minimum. In general, the overall result is reasonably good to predict the mechanical properties of anisotropic plates.